Embryonal rhabdomyosarcoma of the chest wall: A case report and review of the literature - Mysorekar Vijaya; Harish K; Kilara Nalini; Subramanian Murali; Giridhar A (Wolters Kluwer Medknow Publications, 2008)
Embryonal rhabdomyosarcoma is a soft-tissue sarcoma which has a predilection for the head and neck area, genitourinary tract and the extremities. We report a rare case of embryonal rhabdomyosarcoma of the chest wall in an 8-year-old girl, presenting as a destructive tumor in the rib and clinically and radiologically mimicking Ewing′s sarcoma. Histopathological examination showed a small round cell tumor. Immunohistochemically, the positivity for muscle markers desmin and myogenin in the tumor cells proved to be useful for making a definitive diagnosis of embryonal rhabdomyosarcoma. Cytogenetic analysis revealed a high level of aneuploidy in the tumor cells, with double-minutes and additional chromosomal structural aberrations. The patient is responding well to chemotherapy.